Protocol for an adaptive platform trial of intended service user-derived interventions to equitably reduce non-attendance in eye screening programmes in Botswana, India, Kenya and Nepal - Min Kim; David Macleod; Michael Gichangi; Andrew Bastawrous; Matthew J Burton; Jacqueline Ramke; Oathokwa Nkomazana; James R Carpenter; Sailesh Mishra; Shalinder Sabherwal; Luke Allen; Sarah Karanja; et al. (BMJ Open)
Introduction Only 30%–50% of people referred to clinics during community-based eye screening are able to access care in Botswana, India, Kenya and Nepal. The access rate is even lower for certain population groups. This platform trial aims to test multiple, iterative, low-risk public health interventions and simple service modifications with a series of individual randomised controlled trials (RCT) conducted in each country, with the aim of increasing the proportion of people attending.Methods and analysis We will set up a platform trial in each country to govern the running of a series of pragmatic, adaptive, embedded, parallel, multiarm, superiority RCTs to test a series of service modifications suggested by intended service users. The aim is to identify serial marginal gains that cumulatively result in large improvements to equity and access. The primary outcome will be the probability of accessing treatment among the population group with the worst access at baseline. We will calculate Bayesian posterior probabilities of clinic attendance in each arm every 72 hours. Each RCT will continually recruit participants until the following default stopping rules have been met: >95% probability that one arm is best; >95% probability that the difference between the best arm and the arms remaining in the trial is <1%; or 10 000 people have been recruited. Lower thresholds may be used for RCTs testing interventions with very low risks and costs. The specific design of cluster RCTs will be determined by our research team once the intervention is known, but the population and outcome will be the same across all trials.This adaptive platform trial will be used to identify effective service modifications, driving continuous improvements in access.Ethics and dissemination This trial has been approved by the research ethics committee at the London School of Hygiene & Tropical Medicine (ref: 29549). Approvals for individual interventions will be sought from UK and local ethics committees. Results will be shared via local workshops, social media and peer-reviewed publications.Trial registration number ISRCTN53970958.